2022
DOI: 10.1177/19417381221093045
|View full text |Cite
|
Sign up to set email alerts
|

Slipped Capital Femoral Epiphysis Associated With Athletic Activity

Abstract: Background: Little data exist regarding the association of slipped capital femoral epiphysis (SCFE) and sporting activities. Hypothesis: There is no association between SCFE and sporting activities. Study Design: Retrospective review of all SCFE cases at our institution from 2010 through March 2021. Level of Evidence: Level 3. Methods: All patients with idiopathic SCFE were reviewed looking for the presence/absence of sporting activities and symptom onset. Also collected were the age, symptom duration, and wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This is especially important for primary care, emergency medicine, and sports medicine health care providers, as a recent study demonstrated that 1/3 of patients with SCFE have a history of athletic activity associated with their symptoms. 25…”
Section: Background and Rationale For The Studymentioning
confidence: 99%
“…This is especially important for primary care, emergency medicine, and sports medicine health care providers, as a recent study demonstrated that 1/3 of patients with SCFE have a history of athletic activity associated with their symptoms. 25…”
Section: Background and Rationale For The Studymentioning
confidence: 99%
“…There is scarce data regarding sports activity and SCFE. Sports activities that impose both vertical stress such as running and rotational stress, like basketball or soccer, might have a higher incidence of SCFE (15). There is a potential correlation between sports participation and occurrence of SCFE, but few studies have examined the return to previous PA in these patients.…”
Section: Groupmentioning
confidence: 99%